Prevalence of chronic headache in workers in a Brazilian industry - Ferreira, Pablo Guarisco; Ricardi, Lara Henriqueta Bussolaro; Santos, Mauricio Bedim dos; César, Alcântara Ramos de Assis (Headache Medicine, 2024)
Introduction. Primary headaches and sleep disorders are closely related conditions. The global prevalence of chronic headache reaches values of 4.6%, while in Brazil it corresponds to 6.9%. Up to 50% of patients with migraine report insomnia. The recurrence of headaches generates important economic losses and affects the patient’s quality of life, with tension type headache and migraine accounting for 6.5% of years lived with disability worldwide. Objective. To calculate the prevalence of chronic headaches in workers in an industry and evaluate the association with work shifts and sleep disorders. Methodology. This is an analytical cross-sectional observational study. The research was carried out remotely, using an electronic form via the Google Forms® platform. The prevalence of chronic headache per work shift was calculated, the independence of the variables was verified using the Chi-Square test, binary logistic regression was used by estimating the odds ratio and 95% confidence intervals were considered, to express the degree of association between the independent variables and the presence of chronic headache. The research project was approved by the Research Ethics Committee of the Health Sciences Sector of the Federal University of Paraná. Results. The global prevalence of chronic headache was higher than the general population (12.43%). No statistically significant association was found between the presence of chronic headache and work shift (p=0.999), increased sleep latency (p=0.087), short sleep duration (p=0.754), restorative sleep (p=0.348) and daytime sleepiness (p=0.910). Conclusion. There was an increased prevalence of chronic headache in relation to that described in the global and national literature for the general population. In the sample, it was independent of clinically significant changes in sleep and work shift, which may suggest the possibility of individual adaptation of the worker to the work shift.